Hetero‐trans‐β‐glucanase, an enzyme unique to Equisetum plants, functionalizes cellulose - Simmons, Thomas J. (Plant J, 2015)
Cell walls are metabolically active components of plant cells. They contain diverse enzymes, including transglycanases (endotransglycosylases), enzymes that ‘cut and paste’ certain structural polysaccharide molecules and thus potentially remodel the wall during growth and development. Known transglycanase activities modify several cell‐wall polysaccharides (xyloglucan, mannans, mixed‐linkage β‐glucan and xylans); however, no transglycanases were known to act on cellulose, the principal polysaccharide of biomass. We now report the discovery and characterization of hetero‐trans‐β‐glucanase (HTG), a transglycanase that targets cellulose, in horsetails (Equisetum spp., an early‐diverging genus of monilophytes). HTG is also remarkable in predominantly catalysing hetero‐transglycosylation: its preferred donor substrates (cellulose or mixed‐linkage β‐glucan) differ qualitatively from its acceptor substrate (xyloglucan). HTG thus generates stable cellulose–xyloglucan and mixed‐linkage β‐glucan–xyloglucan covalent bonds, and may therefore strengthen ageing Equisetum tissues by inter‐linking different structural polysaccharides of the cell wall. 3D modelling suggests that only three key amino acid substitutions (Trp → Pro, Gly → Ser and Arg → Leu) are responsible for the evolution of HTG's unique specificity from the better‐known xyloglucan‐acting homo‐transglycanases (xyloglucan endotransglucosylase/hydrolases; XTH). Among land plants, HTG appears to be confined to Equisetum, but its target polysaccharides are widespread, potentially offering opportunities for enhancing crop mechanical properties, such as wind resistance. In addition, by linking cellulose to xyloglucan fragments previously tagged with compounds such as dyes or indicators, HTG may be useful biotechnologically for manufacturing stably functionalized celluloses, thereby potentially offering a commercially valuable ‘green’ technology for industrially manipulating biomass.